An Evaluation of the Teachers Mate 1 (TM1) Laptop for Pre-tertiary school Teachers using the Consumer-Oriented Evaluation Approach in the Tamale Metropolis - Iddrisu, Hassan Mubarik (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study evaluates the Teachers Mate 1 (TM1) laptop initiative for pre-tertiary school teachers in Tamale Metropolis, Ghana, using the Consumer-Oriented Evaluation Model. The initiative aimed to enhance teaching and learning through laptop distribution. Guided by Scriven’s model, the study assessed the laptops’ effectiveness from the users’ perspective. A cross-sectional survey design was employed, with data collected from 260 teachers across eight senior high schools using structured questionnaires. The sample was determined using the Yamane formula, with proportional random sampling ensuring representation. Data analysis, conducted using SPSS (version 26), revealed that 56.5% of respondents felt the laptops were not worth their cost, and 47.3% expressed dissatisfaction due to quality and performance issues. Gender disparities emerged, with male teachers more likely to own additional laptops. Despite these concerns, 63.5% of respondents rated the initiative positively, indicating mixed perceptions. The study underscores the need for rigorous pre-implementation evaluations, incorporating user feedback and quality assurance measures. It recommends a structured stakeholder engagement process, including teachers, policymakers, and technology experts, to ensure future educational technology initiatives align with user needs and expectations.